Cronos - Alvarez, Javier 1956- (The Criterion collection, 2010)
Kindly antiques dealer Jesus Gris happens upon an ancient golden device, and soon finds himself possessor and victim of its sinister, addictive powers, as well as the target of a mysterious, crude American named Angel